THE ARMY OF THE CRIMEAN KHANATE IN THE MILITARY CAMPAIGNS AGAINST THE MOLDOVAN PRINCIPALITY (1484–1538) (Південний архів (історичні науки), 2026)
The article examines the features of the military campaigns of the Crimean Khanate, as an ally of the Ottoman Empire, against the Moldavian Principality during 1484-1538, analyzes the number, armament and tactics of the Crimeans, the process of Moldova’s transformation into a vassal state of the Porte is shown. The purpose of the study is a comprehensive analysis of the participation of the Crimean Khanate’s army in hostilities against Moldova in 1484-1538. The methodological basis of the article is the general scientific principles of historicism, objectivity and systematicity. The historical-genetic method allows us to trace changes in political relations between the Porte, the Crimean Khanate and Moldova. The historical-comparative method allows us to compare the army of the Moldavian Principality, the Crimean Khanate and the Ottoman Empire, primarily their numerical composition, tactics and features of military art. Scientific novelty. The article shows the significant role of the Crimean Tatars in the conquest of Moldova by the Ottoman Empire. A large array of contemporary narrative sources, works of Romanian, Turkish and Ukrainian researchers are used. The reports of the contemporary chronicles and annals about the battles of 1518 and 1538 are critically examined – mainly about the number of participants, the course and consequences. It is proven that the actions of the Crimeans weakened the ability of Moldova to resist the Turks, dealt a powerful blow to the mobilization capabilities of the principality, and also made a significant contribution to the tactical and field reconnaissance of the Ottomans. It is traced that Moldova was never able to find effective allies among other states, and Poland, due to the conflict over Pokuttya, acted as a situational ally of the Porte, in particular in the campaign of 1538. Conclusions. The Turkish sultans began to involve the Tatars for raids on the Moldavian territories from the second half of the 15th century, as an instrument of pressure, intimidation and punishment. The Tatar raid of 1518 ended in failure for them, as the Moldavian army, thanks to night maneuvers, was able to defeat the Crimean camp and pursued the enemy. Relations between Moldova and the Porte significantly worsened during the reign of the lord Petru Rareş. It is proven that the military campaign of the Porte in 1538 had a number of reasons, primarily due to the actions of the Moldavian lord P. Rareş, strategic goals and the need to obtain a bridgehead for further campaigns against European states. It is concluded that the principality in 1538 was unable to fully mobilize the army due to the actions of the Tatars and the resistance of the Moldavian elite (boyars), the lord was unable to give the enemy a decisive battle in a pre-selected place. The Crimean Khanate, thanks to the use of successful tactics and maneuvers, actively contributed to the capture of Moldova by the Ottomans. Due to their high mobility, the Crimeans were engaged in tactical reconnaissance on the battlefield, carried out diversionary maneuvers, and were recruited by the Ottomans to collect fodder and supplies on the territory of Moldova.
Keywords: Crimean Khanate, army, military art, Late Middle Ages, battles, tactics, campaign, Petru Rareș, Ottoman Empire, Principality of Moldova